Unusual sauropod slipping tracks preserved on a biostabilized tidal flat from the Lower Cretaceous of northern Patagonia, Argentina - Heredia, Arturo Miguel (2022)
Several elongated and other crescent-shaped impressions interpreted as dinosaur tracks and preserved on Lower Cretaceous tidal flat deposits from the Agrio Formation (northern Patagonia, Argentina) are studied in detail. These tracks were documented on a palaeosurface showing palaeotopographic differences over a short distance, related to the lateral migration of a tidal channel. A genetic order between biostabilization and bioturbation of the palaeosurface is recognized. Ripples generated within the channel during the flood tide were first biostabilized; there, horseshoe crab trace fossils were produced. Then, the area bearing the tracks studied here was subaerially exposed, with the biostabilized substrate generating a slippery surface. Scanning electron microscope (SEM) analysis of the rims indicates that the microbial mat was disturbed by the trampling. Finally, microbial mats recovered, and some tracks preserve wrinkle marks inside the tracks. Taking into account the substrate properties and track features analized (morphology, size, depth, and orientation), it is concluded that the tracks were produced by dinosaurs, probably small sauropods, trampling on a slippery surface and moving parallel to the channel margin. This study is an unusual case of slipping tetrapod tracks preserved on a biostabilized tidal flat developed in a mixed carbonate-siliciclastic environment.